Legal feasibility regarding the extension of maternity leave (Research, Society and Development, 2021)
Maternity leave is a mother's right; therefore, the State must guarantee it. Notwithstanding the existence of laws that protect breastfeeding, playing a fundamental role, the current legal scenario leads to a reflection regarding the period of leave, especially in view of the legal provision of 120 days leave, with a discrepancy with the child's need in relation to breastfeeding, for a minimum of 6 months of exclusive breastfeeding, as advocated by the World Health Organization and the Ministry of Health. The work aimed to analyze the feasibility of expanding maternity leave by proposing its expansion to at least 180 days, in contrast to what is provided for in Brazilian legislation. It approached the internal legislation, such as Law nº 11.770/08, which created the Citizen Company Program, which allows companies to sign up to extend the leave to 180 days as a form of tax incentive, which, however, implies unequal treatment among female workers. Comparing the current national and international laws regarding maternity leave, it can be seen that there are other countries that provide greater benefits to mothers with longer periods of maternity leave. To prepare the present study, a bibliographic search was carried out in legal texts, doctrine and scientific articles. As a conclusion, respecting the constitutional principles, focused on the individual rights and guarantees of the human being, it is feasible and necessary to extend the period of maternity leave, aiming at the protection of fundamental rights and better personal and professional life conditions for the mother and, consequently, for her child.